2010
DOI: 10.2169/internalmedicine.49.3824
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Aspirin-Induced Gastroduodenal Mucosal Injury in Japanese Patients with Arteriosclerotic Disease

Abstract: Background We aimed to elucidate the risk factors and preventive factors associated with chronic low-dose aspirin (L-ASA)-induced gastroduodenal mucosal injury in Japanese patients with arteriosclerotic disease. Methods This retrospective observational study included 400 L-ASA users who underwent upper gastrointestinal endoscopy. We investigated patients' clinical characteristics, including age, peptic ulcer history, concomitant drugs [i.e. gastric agents, antiplatelet drugs, anticoagulants, non-steroidal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
2
13
1
1
Order By: Relevance
“…Nevertheless human and animal studies have indicated that use of L-ASA causes to mucosal damages in the gastrointestinal system, which might lead to oxidative stress, gastro-duodenal erosion, ulceration, and bleeding [6][7][8][13][14][15][16]. In the present study, we observed histologically gastric and duodenal mucosal injuries induced by use of L-ASA daily for 40 days in agreement with previous reports [13,16].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless human and animal studies have indicated that use of L-ASA causes to mucosal damages in the gastrointestinal system, which might lead to oxidative stress, gastro-duodenal erosion, ulceration, and bleeding [6][7][8][13][14][15][16]. In the present study, we observed histologically gastric and duodenal mucosal injuries induced by use of L-ASA daily for 40 days in agreement with previous reports [13,16].…”
Section: Discussionsupporting
confidence: 92%
“…After screening the titles, abstracts and full text, 13 studies were considered eligible for complete data extraction. Of these, four cohort studies reported on the effect on peptic ulcer, five studies [two cohort and three case–control studies ] on GI bleeding, three studies [two RCTs and one cohort study ] on both GI bleeding and peptic ulcer, and one cohort study on both GI bleeding and CV events. Among nine studies that reported on GI bleeding, six studies indicated the outcomes as upper GI bleeding (UGIB) while the others did not specify the location of the bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs and five cohort studies reported on the effect on peptic ulcer. Only two of the five cohort studies adjusted the effect estimates for potential confounding. A total number of 5407 patients (2608 patients on PPIs) were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…3,4) Reducing the risk of gastrointestinal injury (e.g., gastrointestinal ulcers and gastrointestinal bleeding) is also an important clinical issue from the viewpoint of facilitating continued treatment with antithrombotic drugs. With these points borne in mind, it is essential to prevent and treat thrombotic cardiovascular and cerebrovascular injuries and to select appropriate antithrombotic drugs.…”
mentioning
confidence: 99%
“…With these points borne in mind, it is essential to prevent and treat thrombotic cardiovascular and cerebrovascular injuries and to select appropriate antithrombotic drugs. [2][3][4][5][6][7] However, there are many unresolved questions about the risk of gastrointestinal injury arising from antithrombotic drugs other than low-dose aspirin and the effects of drugs used for the prevention of such injury. Therefore, we carried out a pharmacological study in patients receiving antithrombotic drugs in order to identify the risk factors of gastrointestinal injury associated with antithrombotic drug therapy.…”
mentioning
confidence: 99%